Immunoglobulin G4-Related Mastitis: An Unusual Case of Recurrent Breast Abscess - Shruti BAJAD,; Dhaval TANNA,; Gayatri EKBOTE,; Muzaffar BINDROO,; Kanchan KAUR,; Rajiva GUPTA, (Archives of Rheumatology, 2020)
Immunoglobulin G4-related mastitis (IgG4-RM) is an uncommon entity in clinical practice which has an evolving spectrum of manifestations and presently is of high clinical interest among rheumatologists. Since its closest differential remains breast carcinoma, the importance of describing this entity is in the fact that early diagnosis, awareness and timely management can save the patient from unnecessary surgical intervention and its complications. Tumefactive lesions are considered hallmark of this disease, but rarely abscess may also be the presenting feature. In this article, we describe a 24-year-old female patient of a very unusual case of IgG4-RM presenting as recurrent breast abscess, its successful management and discussion about novel treatment strategies.